Sea surface temperature variability and sea-ice extent in the subarctic northwest Pacific during the past 15,000 years - Max, Lars; Riethdorf, Jan-Rainer; Tiedemann, Ralf; Smirnova, Maria; Lembke-Jene, Lester; Fahl, Kirsten; ürnberg, Dirk; Matul, Alexander; Mollenhauer, Gesine (Paleoceanography, 2012)
Past changes in North Pacific sea surface temperatures and sea-ice conditions are proposed to play a crucial role in deglacial climate development and ocean circulation but are less well known than from the North Atlantic. Here, we present new alkenone-based sea surface temperature records from the subarctic northwest Pacific and its marginal seas (Bering Sea and Sea of Okhotsk) for the time interval of the last 15 kyr, indicating millennial-scale sea surface temperature fluctuations similar to short-term deglacial climate oscillations known from Greenland ice core records. Past changes in sea-ice distribution are derived from relative percentage of specific diatom groups and qualitative assessment of the IP25biomarker related to sea-ice diatoms. The deglacial variability in sea-ice extent matches the sea surface temperature fluctuations. These fluctuations suggest a linkage to deglacial variations in Atlantic meridional overturning circulation and a close atmospheric coupling between the North Pacific and North Atlantic. During the Holocene the subarctic North Pacific is marked by complex sea surface temperature trends, which do not support the hypothesis of a Holocene seesaw in temperature development between the North Atlantic and the North Pacific.